English in Shop Signs: Exploring the Bilingual Creativities Found in the Tourism Landscape in Malang and Batu - Khazanah, Dewianti; Kusumaningputri, Reni; Setiarini, Riskia; Anam, Syamsul; Sampurna, Hadi (English Department, Universitas Negeri Surabaya, 2022)
As popular tourist sites, Malang and Batu in East Java are multicultural and multilingual in nature with at least local languages and national language being used on a daily basis. With globalization and growing markets for business, contacts among their citizens create captivating language/ linguistic landscapes. Many previous research have focused on the vitality and salience of language representations in signboards and discussed the impacts they have on the sociolinguistic reality of the people. This current study, however, explores the bilingual/ multilingual play of the languages used in shop signs in these cities and the possible effects they create. Of 88 signboards under investigation, lexical hybridization- Englishized spelling and hybrid compounding- and bilingual creativity at the syntactic level were the most used strategies. Other textual processes which were commonly found in the signboards are bilingual punning, bilingual rhyming, and mock Englishization. The semantic feature was commonly used as the complementary relationship between language and the content. Effects of these creative processes are projecting modernism, sophistication, association with the international market, ludic effect as an attention-getter, and facilitating memorization.